The justice experiences of students with ADHD symptoms and the relation to classroom climate - Ronkainen, Tiina; Turunen, Annika (2024)
It is suggested that students with ADHD have experienced unfair treatment in school by teachers. The goal of this research was to examine whether students with ADHD symptoms experience their teachers’ behaviour differently from their peers in terms of justice. The second goal of the study was to investigate whether socioemotional support and classroom management are related to justice experiences and whether ADHD symptoms moderate this relation. Data for this study was collected as a part of the InterLearn study (N = 718) among Grade 3 to 4 students. Hierarchical linear regression was used to examine the relation between ADHD symptoms, justice experiences and classroom climate dimensions as well as to examine the moderating effect of ADHD symptoms on justice experiences. Students with ADHD symptoms experienced the classroom less just compared to their peers. Both classroom management and socioemotional support had a positive relation to justice experiences. The interaction of ADHD and classroom management had a significant moderating effect on justice experiences. The same effect was not found with socioemotional support. Based on the results, students with ADHD symptoms experience the classroom to be more unfair than their peers. Socioemotional support and classroom management seem to be important factors in justice experiences for all students. For students with ADHD symptoms the relation of classroom management and justice experiences was stronger than for their peers. The relation of socioemotional support and justice experience did not differ between ADHD groups.